Gradient-Type Methods: A Unified Perspective in Computer Science and Numerical Analysis. (20th July 2011) - Fanelli, Stefano
Abstract : This paper presents a general and comprehensive description of Optimization Methods, and Algorithms from a novel viewpoint. It is shown, in particular, that Direct Methods, Iterative Methods, and Computer Science Algorithms belong to a well-defined general class of both Finite and Infinite Procedures, characterized by suitable descent directions.